1979
DOI: 10.1104/pp.63.5.841
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of Anthocyanin Synthesis

Abstract: Light-dependent anthocyanin synthesis is a typical high irradiance response (HIR) of plant photomorphogenesis. The spectral sensitivity of this response in young seedlings of cabbage and tomato is strongly affected by the length and mode of application of the Ught treatments. This observation suggests that the different experimental conditions, used in different action spectroscopy studies, might have been responsible, at least in part, for some of the reported differences in the characteristics of the HIR act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…For most of the systems, assigned to group I, FR and BL are the most effective regions. For tomato and rye seedlings (MANCI-NELLI 1981, MANCINELLI and WALSH 1979, RABINO et al 1977, the UV jBL region is much more effective than the Rand FR ones.…”
Section: The Spectral Sensitivity Of Anthocyanin Production Under Conmentioning
confidence: 98%
See 2 more Smart Citations
“…For most of the systems, assigned to group I, FR and BL are the most effective regions. For tomato and rye seedlings (MANCI-NELLI 1981, MANCINELLI and WALSH 1979, RABINO et al 1977, the UV jBL region is much more effective than the Rand FR ones.…”
Section: The Spectral Sensitivity Of Anthocyanin Production Under Conmentioning
confidence: 98%
“…Examples: seedlings of white mustard (KANDELER 1958, MOHR 1957, WAGNER and MOHR 1966, black mustard (KANDELER 1958), leaf mustard (KANDELER 1958), red cabbage (KANDELER 1958, Ku-TAI 1972, Ku and MANCINELLI 1972, MANCINELLI and WALSH 1979, RABINO et aI. 1977, SIEGELMAN and HENDRICKS 1957, tomato WALSH 1979, RABINO et aI.…”
Section: The Spectral Sensitivity Of Anthocyanin Production Under Conmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies in my laboratory (10,16) have shown that the R/FR effectiveness ratio for anthocyanin production under continuous irradiation can be significantly affected by the duration and the photon flux ofthe light treatments. However, specific studies on the relationships between the state of phytochrome, as defined by X and H, and anthocyanin production, under continuous light treatments, at values of 4 different than those established by R and FR, had not been carried out.…”
mentioning
confidence: 99%
“…However, specific studies on the relationships between the state of phytochrome, as defined by X and H, and anthocyanin production, under continuous light treatments, at values of 4 different than those established by R and FR, had not been carried out. The purpose of this study was to determine the extent of the differences in the pattern of interaction between light quality and quantity on phytochrome-mediated anthocyanin production in the seedlings of two species, Brassica oleracea L. and Lycopersicon esculentum Mill., which show large differences in the sensitivity of the response to R and FR (10,16,20). Anthocyanin production in both species shows a marked response to BL, which is mediated by cryptochrome (21 92,1990 of streptomycin (200 ,ug/mL; 8 mL per dish) and were incubated in darkness until the beginning of the light treatments, which started 4 d after sowing.…”
mentioning
confidence: 99%